Sci-Anime2021 / Humaira Batrisyia Norzaimi … [et al.] - Norzaimi, Humaira Batrisyia; Norzaimi, Iqlima Zulaikha; Norzaimi, Qaisara Madiha; Abdul Rahman, Wahida; Ku Abdul Halim, Ku Liana Farhany (Faculty of Computer and Mathematical Sciences, 2021)
E-Content development, especially in Science, is very important during Covid-19 era. It helps students to understand more due to the limitation of physical class during Covid-19 outbreak. This e-content name Sci-Anime has been developed to help students to understand more in science subjects. Sci-Anime is a type of E-Content that focuses on laboratory experiments which relate to science subjects for primary school students. Through this animation, the understanding of students towards science and laboratory experiments become very interesting and more interactive. Moreover, students can observe digitally how the experiments are conducted. Apart from that, this e-content will be developed with simple assessment after a few class sessions. Therefore, during PdPR (Pengajaran dan Pembelajaran Di Rumah) the learning will be more fun and teachers can apply this e-content as support content during Google Meet session.